2017
DOI: 10.1016/j.jbi.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Can teamwork and situational awareness (SA) in ED resuscitations be improved with a technological cognitive aid? Design and a pilot study of a team situation display

Abstract: Overall, this pilot study implies that a situation display could facilitate better teamwork and team communication in the resuscitation event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 38 publications
0
63
0
Order By: Relevance
“…One of two subject matter experts (J-MG and MH) experienced in using the Clinical Teamwork Scale (CTS) directly observed simulations in real time and measured teamwork using the CTS, a validated instrument that measures overall teamwork and 15 specific elements in five overarching domains in addition to overall teamwork: communication, decision-making, role responsibility (leadership and followership), situational awareness/resource management and patient-friendliness 19. CTS was selected because the authors were skilled in its use having developed it over a decade ago with a diverse team (that included one of the founders of crew resource management), it was designed specifically to allow quick assessments of teamwork during rapidly moving clinical emergencies, it is free, and has been successfully used by us and numerous others to measure teamwork in emergent clinical scenarios similar to our intended purpose: paediatric resuscitations, obstetrics, trauma, advanced cardiac life support and emergency medical services 20–27. Evaluators rate the performance of the care team using a Likert scale of zero (unacceptable) to 10 (perfect) and are given space to insert narrative comments.…”
Section: Methodsmentioning
confidence: 99%
“…One of two subject matter experts (J-MG and MH) experienced in using the Clinical Teamwork Scale (CTS) directly observed simulations in real time and measured teamwork using the CTS, a validated instrument that measures overall teamwork and 15 specific elements in five overarching domains in addition to overall teamwork: communication, decision-making, role responsibility (leadership and followership), situational awareness/resource management and patient-friendliness 19. CTS was selected because the authors were skilled in its use having developed it over a decade ago with a diverse team (that included one of the founders of crew resource management), it was designed specifically to allow quick assessments of teamwork during rapidly moving clinical emergencies, it is free, and has been successfully used by us and numerous others to measure teamwork in emergent clinical scenarios similar to our intended purpose: paediatric resuscitations, obstetrics, trauma, advanced cardiac life support and emergency medical services 20–27. Evaluators rate the performance of the care team using a Likert scale of zero (unacceptable) to 10 (perfect) and are given space to insert narrative comments.…”
Section: Methodsmentioning
confidence: 99%
“…A couple of research projects focus on the application of human factors engineering to design health IT for teams. Two research teams in Ottawa, Canada 48 , 5052 and at the University of Illinois 53 used various human factors methods that provided input to build shared team displays for supporting cognitive work and communication during resuscitations. In Canada, Parush et al, designed a smart display to support cognitive work and team communication during ED resuscitation 48 , 5052 .…”
Section: Human-centered Design Of Health Itmentioning
confidence: 99%
“…Two research teams in Ottawa, Canada 48 , 5052 and at the University of Illinois 53 used various human factors methods that provided input to build shared team displays for supporting cognitive work and communication during resuscitations. In Canada, Parush et al, designed a smart display to support cognitive work and team communication during ED resuscitation 48 , 5052 . Using multiple methods (e.g., interview of ED clinicians, observation of live resuscitations), they identified key information needs, and then implemented an iterative human-centered design process to develop a prototype for the shared situation display 48 , 52 .…”
Section: Human-centered Design Of Health Itmentioning
confidence: 99%
“…In the chaotic environment of a cardiac arrest, identification of error and other human factors is an important challenge [30]. There is an increasing body of literature to support the use of simulation to assess performance, and studies surrounding the use of decision support tools and systems in simulated critical situations are now emerging [38,39,24,27]. However, we have demonstrated that self-reporting of performance is misleading and should be avoided when studying such phenomenon.…”
Section: Resultsmentioning
confidence: 96%
“…Failures within teams and poor communication are among the most common reasons for adverse medical events [27,28]. Previous decision support tools were designed solely to support the team leader, failing to recognise the importance of effective communication and team cohesion, whereby team situational awareness could then be lost.…”
Section: Discussionmentioning
confidence: 99%